The Community Health Worker (CHW) Common Indicators Project: Engaging CHWs in Measurement to Sustain the Profession - Rodela, Keara; Wiggins, Noelle; Maes, Kenneth; Campos-Dominguez, Teresa; Adewumi, Victoria; Jewell, Pennie; Mayfield-Johnson, Susan (Frontiers in Public Health, 2021)
Despite progress in documenting the outcomes of interventions led by CHWs, the lack of standardized measures to evaluate CHW programs and policies has made it impossible to aggregate data across programs and regions, impeding commitment to sustainable, long-term financing of CHW programs and positions. Lack of comprehensive and easy-to-use indicators hampers the ability of many community-based programs to reliably report outcomes to funders. Lack of attention to the processes by which CHWs achieve outcomes has made it difficult to conclusively demonstrate the importance and effectiveness of particular CHW core roles, skills, and qualities. To address these issues, in 2015 researchers (including CHWs) from five states formed the national CHW Common Indicators (CI) Project. The purpose of the CI Project is to contribute to the integrity, sustainability, and viability of CHW programs through the collaborative development and adoption of a set of common process and outcome constructs and indicators for CHW practice and CHW program implementation. Since its organizing Summit in 2015, CHWs have been at the forefront of the CI Project. Supported by funding from the Centers for Disease Control and Prevention in 2019-2020, the CI Project was able to enhance the engagement of CHWs through a series of stakeholder engagement activities. These activities, along with a systematic literature review, were used to develop evaluation indicators for 10 of the 24 constructs previously identified through a participatory process. Results of the work conducted during 2019-2020 indicate that it is possible to actively engage CHWs in a project that aims to identify common evaluation indicators in the midst of a pandemic. However, doing so effectively requires thoughtful planning, skillful use of popular education methodology, and a team that is aligned around common goals and principles.